The Donbas conflict: Opposing interests and narratives, difficult peace process - Sabine Fischer (Stiftung Wissenschaft und Politik (SWP), 2019)
In 2014, in response to the Ukrainian 'Euromaidan', Russia annexed Crimea and provoked a war in eastern Ukraine. The ensuing conflict still claims lives today. For the past five years Germany and its Western partners have been trying to resolve the conflict politically, to date without success. The Minsk ceasefire agreements of 2014 and 2015 have still not been implemented. All the directly involved actors bear responsibility. The separatist "People's Republics" in Donetsk and Luhansk have established dictatorial quasi-state structures but remain almost completely dependent on Moscow. Russia refuses to acknowledge its role as a party to the conflict. Ukraine has fulfilled some of its obligations under the Minsk Agreements, but neglected others. The situation is exacerbated by negative dynamics on all levels. Kyiv and the "People's Republics" are drifting steadily apart, while millions living along the line of contact experience terrible humanitarian suffering. This threatens to establish a state of permanent poverty and underdevelopment in the regions affected by the conflict. The European Union and its member states pursue a division of labour. Brussels maintains Union-wide sanctions against Russia and forges ahead with implementing the Association Agreement with Ukraine. Germany and France conduct peace talks in the so-called Normandy Format. All conflict parties must be reminded to avoid escalation risks. Much greater attention must be directed to the local level and especially the humanitarian crisis. Action at this level is limited in reach but imperative for progress towards peace.
Keywords: 320